Strategi Generasi Muda Kepulauan Sangihe Perbatasan Indonesia-Filipina dalam Ketahanan Budaya di era Digital - Steven Sumolang; Neni Kumayas; Oldrie Chaterina Sorey; Janeke Peggy Slippy (Prosiding Seminar Nasional Ilmu Pendidikan, 2025)
The young generation is a group of people aged 15-35 who are passionate about changing the world, creative, and energetic. The young generation is often considered an agent of change who can bring positive changes in society. In the digital era, there is a need for efforts to preserve and develop regional cultural wealth so that it remains relevant and known by the younger generation. Local culture can help young people develop a sense of pride in their identity and cultural heritage. The Sangihe Islands in the north of North Sulawesi Province, on the Indonesia-Philippines border, have a variety of local cultures, ranging from historical relics, folk beliefs, arts, traditional ceremonies, traditions of managing natural resources both sea and land, the Sasahara sea language, and the tradition of going to sea that makes the Sangihe people excellent sailors. Being in the Indonesia-Philippines border area and as a spice trade route since ancient times has opened up for changes in the culture of society. And the current development with modernization that has invaded the cultural resilience of its people has entered the outermost islands such as Sangihe Talaud. The young generation is currently a major player in the digital world. This article raises the issue of the strategy of the young generation in cultural resilience in the digital era. That the young people of Sangihe play a role in elevating their local culture which is threatened with erosion. Their various social media platforms with creative efforts elevate the nature and culture of Sangihe Talaud, and have proven successful in rediscovering local cultural values. Sangihe Talaud with its natural potential and diverse arts and culture can be a social capital in the cultural resilience of Sangihe Regency as the northern gateway to eastern Indonesia, as the front line of the archipelago on the edge of the Pacific.